Livelihood Transformation among Hilsa Fishing Households in South Govindia Village, Chandpur District, Bangladesh.: Transformasi Penghidupan pada Rumah Tangga Nelayan Hilsa di Desa Govindia Selatan, Distrik Chandpur, Bangladesh. - Md. Hasan Khan; Dr. Md. Ruhul Amin; Md. Nur Uddin Hossain; Md. Al Amin; Tahmina Akter (Yayasan Nurul Musthafa, 2026)
The Hilsa fishery has long underpinned livelihoods and local trade in South Govindia Village, Chandpur District, but recent socio-environmental shifts are reshaping household economies. This study specifically investigates how ecological pressures and market–institutional factors drive a transition from Hilsa-dependent livelihoods toward diversified income strategies among fishing households. Between January and June 2024, we used a mixed-methods design: a stratified random household survey of 210 fishing households, 12 key informant interviews, four focus group discussions, and participant observation; quantitative data were analyzed with descriptive and inferential statistics and qualitative data through thematic coding. Findings cluster into two main themes: (1) ecological–production stress, evidenced by declining catches, seasonal fishing bans, and climate-related river changes that reduce household fishing income; and (2) market–institutional vulnerabilities, including dependence on intermediaries, limited market bargaining power, and inadequate, short-term compensation that together increase indebtedness and push households toward nonfishing income sources (wage labor, small trade, migration, and aquaculture). Women’s growing role in supplementary activities partly cushions income loss but does not fully offset structural insecurity. The study contributes empirical evidence of a livelihood shift from mono-dependent fishing to diversified survival strategies and argues that targeted, integrated policies—linking cooperative marketing, access to credit, and participatory fisheries governance—are needed to support sustainable economic resilience in Hilsa-dependent communities. [Perikanan Hilsa telah lama menjadi penopang penghidupan dan perdagangan lokal di Desa Govindia Selatan, Distrik Chandpur, namun pergeseran sosial-lingkungan yang terjadi baru-baru ini sedang mengubah ekonomi rumah tangga. Penelitian ini secara khusus menyelidiki bagaimana tekanan ekologis dan faktor-faktor institusional-pasar mendorong transisi dari penghidupan yang bergantung pada Hilsa menuju strategi pendapatan yang beragam di kalangan rumah tangga nelayan. Antara bulan Januari dan Juni 2024, kami menggunakan desain metode campuran: survei rumah tangga acak bertingkat terhadap 210 rumah tangga nelayan, 12 wawancara informan kunci, empat diskusi kelompok terpumpun (FGD), dan observasi partisipan; data kuantitatif dianalisis dengan statistik deskriptif dan inferensial serta data kualitatif melalui pengodean tematik. Temuan mengelompok ke dalam dua tema utama: (1) tekanan produksi-ekologis, dibuktikan dengan menurunnya hasil tangkapan, larangan menangkap ikan musiman, dan perubahan sungai terkait iklim yang mengurangi pendapatan rumah tangga dari menangkap ikan; serta (2) kerentanan institusional-pasar, termasuk ketergantungan pada perantara, terbatasnya daya tawar pasar, dan kompensasi jangka pendek yang tidak memadai yang secara bersama-sama meningkatkan utang dan mendorong rumah tangga ke arah sumber pendapatan non-perikanan (pekerja upahan, perdagangan kecil, migrasi, dan akuakultur). Peran perempuan yang semakin berkembang dalam aktivitas tambahan sebagian turut meredam hilangnya pendapatan, namun tidak sepenuhnya menutupi ketidakamanan struktural. Studi ini memberikan bukti empiris tentang pergeseran penghidupan dari ketergantungan tunggal pada perikanan menuju strategi bertahan hidup yang beragam dan berargumen bahwa kebijakan yang terarah dan terintegrasi—yang menghubungkan pemasaran kooperatif, akses kredit, dan tata kelola perikanan partisipatif—diperlukan untuk mendukung ketahanan ekonomi yang berkelanjutan di komunitas yang bergantung pada Hilsa.]